Detection of fire prone environment using Thermal Sensing Drone. Issue 1 (February 2021) - Nithyavathy, N; Arun Kumar, S; Rahul, D; Satheesh Kumar, B; Shanthini, E R; Naveen, C.
Abstract: Drones of various types are currently in great demand because of their flexible applications to facilitate human life. At acceptable constant quality levels, they can perform tasks in a repetitive manner. A drone is intended and built in the current work to evaluate the area vulnerable to fire and its surface area at an altitude of 10 meters. In the event of a forest fire disaster, evaluating the impacted area is very complicated. This approach needs to be adaptable and easily controlled in order to solve it. Thus, both the manual and autopilot mode are built and controlled by a quad copter drone with an ardupilot, which drives the drone to the specified location. The drone is fed with the specification of the Global Positioning System ( GPS) and flies with the aid of an ardupilot to the spot. With the aid of a thermal imaging sensor, the drone senses the surface area with its captured image. With the aid of coding dumped in it, the image is sent to the base station and the vision building is achieved with the help of the thermal camera fitted in the front part of the drone and then it interacts with the base station where it is possible to view the surface area. This allows average individuals to recognize the region impacted by the tragedy and to predict the amount of impact they have made in a shorter period of time. Human interference is minimized by this detection method in the areas affected by fire with the extent of fire prediction.